IMPLEMENTASI PENDEKATAN PERBANDINGAN HUKUM DALAM PENELITIAN HUKUM NORMATIF - Hermit Purwedy Zendrato; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines the implementation of the comparative law approach in normative legal research and formulates an operational model that preserves doctrinal rigor while remaining sensitive to institutional, historical, and cultural contexts. The research uses normative legal research with statutory, conceptual, case, historical, and comparative approaches. Primary legal materials consist of legislation and judicial principles, while secondary materials include comparative law scholarship and journal articles published from 2020 to 2026. The materials are analyzed through identification of the legal problem, determination of the tertium comparationis, selection of comparable jurisdictions, contextual description, functional and structural comparison, critical evaluation, and normative synthesis. The study finds that comparative law is not merely the juxtaposition of foreign rules. Its validity depends on equivalent units of comparison, transparent jurisdiction selection, attention to formal and informal institutions, and a reasoned assessment of contextual compatibility. The proposed model consists of six connected stages: problem formulation, comparator design, material verification, contextual reconstruction, evaluative comparison, and controlled legal adaptation. This model enables comparative findings to strengthen interpretation, legal reform, and the development of Indonesian legal scholarship without reducing foreign law to an uncritical source of imitation.